(untitled) (International Journal of Geoscience, Engineering and Technology, 2025)
This study investigated the creeping phenomena on Presidente Prudente Street, Jardim São Paulo neighborhood, in Teófilo Otoni – MG, using an approach that combined literature review, field analysis, and the application of guidelines from the Ministry of Cities for risk mapping. During the field survey, various indicators of creeping were observed, such as trees with abnormal inclinations, soil cracks, and abandoned buildings with signs of structural deformation. Based on these observations, the area was preliminarily classified as Medium Risk (R2), although this assessment is an initial interpretation. The instability of the terrain and the presence of mass movements indicate potential risks to the safety of constructions in the studied area. This research identified physical signs of these geological phenomena, demonstrating the vulnerability of this location and warning against unplanned urbanization. The study contributes to understanding the geological processes affecting Teófilo Otoni, providing a basis for future studies and interventions aimed at safety and sustainable urban planning in the region.